Problematyka lokali wyborczych dostosowanych do potrzeb wyborców niepełnosprawnych w wyborach samorządowych 2014 roku w świetle działań Rzecznika Praw Obywatelskich - Zbieranek, Jarosław (Polityka i Społeczeństwo, 2021)
Despite the introduction of alternative voting procedures in the Polish electoral system, a significant part of disabled or elderly voters declare that they are willing to vote in a traditional way — at the polling station. The survey carried out in March 2014 shows that over 80% of respondents indicated voting at polling stations as the preferred way of voting in an election. A very important issue is the appropriate adaptation of polling stations to the needs of voters with limited mobility. The Electoral Code significantly increases the number of polling stations adapted to the needs of people with disabilities. The head of the commune shall adapt at least 1∕5 of stations by 31 December 2014. However, as indicated by the results of the inspections carried out by the Ombudsman (Human Rights Defender) in November 2014, the vast majority of polling stations designated by the commune as adapted to the needs of people with disabilities were in fact not accessible for this group of voters. At 179 polling sta-tions inspected by employees of the Office of the Ombudsman shortcomings were noted in 151, which accounted for 84% of all buildings visited. It is therefore necessary to take extensive measures for the real fulfilment of the requirements specified by law. A significant proportion of the voters surveyed expressed the view that of all the possible facilities, free transport of voters to the polling station would be the most useful in the next election.